ab(c²+d²)-a²cd–b²cd
Answers
Answered by
0
Answer:
ab (c2 + d2) – a2cd – b2cd
= abc2 + abd2 – a2cd – b2cd
= abc2 – a2cd – b2cd + abd2
= ac (bc – ad) – bd (bc – ad)
= (bc – ad) (ac – bd)
Answered by
4
Answer:
(bc-ad) ( ac-bd )
Step-by-step explanation:
abc2 + abd2 – a2cd – b2cd
= abc2 – a2cd – b2cd + abd2
= ac (bc – ad) – bd (bc – ad)
= (bc – ad) (ac – bd)
hooope it helps you
Similar questions
Hindi,
1 month ago
English,
1 month ago
World Languages,
1 month ago
India Languages,
2 months ago
Math,
2 months ago
Math,
11 months ago
Geography,
11 months ago
Hindi,
11 months ago